Homozygosity Mapping Reveals Population History and Trait Architecture in Self-Incompatible Pear (Pyrus spp.) - Kumar, Satish; Deng, Cecilia Hong; Hunt, Martin; Kirk, Chris; Wiedow, Claudia; Rowan, Daryl; Wu, Jun; Brewer, Lester (Frontiers in Plant Science, 2021)
Runs of homozygosity (ROH) have been widely used to study population history and trait architecture in humans and livestock species, but their application in self-incompatible plants has not been reported. The distributions of ROH in 199 accessions representing Asian pears (45), European pears (109) and interspecific hybrids (45) were investigated using genotypingby-sequencing in this study. Fruit phenotypes including fruit weight, firmness, Brix, titratable acidity, and flavour volatiles were measured for genotype-phenotype analyses. The average number of ROH and the average total genomic length of ROH were 6 and 11 Mb, respectively, in Asian accessions, and 13 and 30 Mb, respectively, in European accessions.Significant associations between genomic inbreeding coefficients (FROH) and phenotypes were observed for 23 out of 32 traits analysed. An overlap between ROH islands and significant markers from genome-wide association analyses was observed. Previously published quantitative trait loci for fruit traits and disease resistances also overlapped with some of the ROH islands. A prominent ROH island at the bottom of linkage group 17 overlapped with a recombination-supressed genomic region harbouring the selfincompatibility locus. The observed ROH patterns suggested that systematic breeding of European pears would have started earlier than of Asian pears. Our research suggest that FROH would serve as a novel tool for managing inbreeding in gene-banks of self-incompatible plant species. ROH mapping provides a complementary strategy to unravel the genetic architecture of complex traits, and to evaluate differential selection in outbred plants. This seminal work would provide foundation for the ROH research in self-incompatible plants.